Über die Stellung von Corynetes rufus Kraatz im System der Cleridae (Coleoptera). - Winkler, Josef Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1960)
Position of the species Corynetes rufus Kraatz in system of the Cleridae has been studied. With respect to its specific features the species is arranged within the new genus Romanaeclerus.Nomenclatural ActsRomanaeclerus Winkler, 1960 (Cleridae), gen. n.rufus (Kraatz, 1899) (Romanaeclerus), comb. n. hitherto Corynetes rufus Kraatz, 1899